Contextualizing primary school teachers’ perception of the parent-child relationship - Saragih, Erikson; Hashim, Haida Umiera; Junaid, Ayesha; Nababan, Tiarnida; Nababan, Tiorika Mariana (Psikologia: Jurnal Pemikiran dan Penelitian Psikologi, 2024)
The most crucial relationships for students' social and emotional development and wellbeing are those between parents and pupils. While there is a wealth of research on programs to enhance parent-child connections, few are designed for use by educators in early education and care settings. This study aims to describe teachers' comprehension of the parent-child relationship concerning social and emotional development, the teacher's role in fostering the parent-child relationship, and the forms of teacher support in the parent-child relationship. This research method is a qualitative descriptive study with a phenomenological design involving six school principals and twenty teachers at the elementary education level as research subjects. The results showed that early education teachers were reluctant to contact parents, although acknowledging the importance of parent-child interactions. Teachers tended to be unwilling to impart their knowledge to parents since it was primarily implicit and derived from observations and real-world experiences. Teachers want theoretical, supported evidence methods to deepen their understanding and enhance everyday activities that strengthen parent-child interactions. The results are crucial for creating a parent-child connection program led by educators for implementation in educational and childcare facilities. A comprehension of educators' regular practices, their function in promoting parent-child connections, and children's social and emotional development should be explored to guide the creation of an educator program. These results are crucial for creating a parent-child connection program developed by educators for use in educational and childcare settings.